Unusual coastal flood impacts in Salmon Valley, McMurdo Sound, Antarctica. Issue 4 (6th May 2016) - Dayton, Paul K.; Hammerstrom, Kamille; Jarrell, Shannon C.; Kim, Stacy; Nordhausen, Walter; Osborne, D.J.; Thrush, Simon F.
Abstract: Large floods bringing significant sediments into the coastal oceans have not been observed in Antarctica. We report evidence of a large flood event depositing over 50 cm of sediment onto the nearshore benthic habitat at Salmon Bay, Antarctica, between 1990 and 2010. Besides direct observations of the sedimentation, the evidence involves a debris flow covering old tyre tracks from the early 1960s, as well as evidence of a considerable amount of sediment transported onto the Salmon Creek delta. We believe that the flood was sourced from the Salmon Glacier and possibly the smaller Blackwelder Glacier. Such floods will be more common in the future and it is important to better understand their ecological impacts with good monitoring programmes.